Percutaneous microwave ablation versus sclerotherapy for large hepatic hemangioma: a multi-center cohort study - Qian Cai; Tong-Gang Qian; Qi-Yu Zhao; Shun-You Feng; Qiao Yang; Yan-Chun Luo; Yu-Qing Dai; Ping Liang; Xiao-ling Yu; Fang-Yi Liu; Zhi-Yu Han; Qiao-Wei Du; et al. (International Journal of Hyperthermia)
Objective The study aimed to compare the effectiveness and safety of ultrasound-guided microwave ablation (MWA) and percutaneous sclerotherapy (PS) for the treatment of large hepatic hemangioma (LHH).Methods This retrospective study included 96 patients who underwent MWA (n = 54) and PS (n = 42) as first-line treatment for LHH in three tertiary hospitals from January 2016 to December 2021. Primary outcomes were technique efficacy rate (volume reduction rate [VRR] > 50% at 12 months), symptom relief rate at 12 months and local tumor progression (LTP). Secondary outcomes included procedure time, major complications, treatment sessions, cost and one-, two-, three-year VRR.Results During a median follow-up of 36 months, the MWA group showed a higher technique efficacy rate (100% vs. 90.4%, p = .018) and symptom relief rate (100% vs. 80%, p = .123) than the PS group. The MWA group had fewer treatment sessions, higher one-, two- and three-year VRR, lower LTP rate (all p < .05), longer procedure time and higher treatment costs than the PS group (both p < .001). MWA shared a comparable major complications rate (1.8% vs. 2.4%, p = .432) with PS. After multivariate analysis, the lesion’s heterogeneity and maximum diameter >8.1 cm were independent risk factors for LTP (all p < .05). In the PS group, lesions with a cumulative dose of bleomycin > 0.115 mg/cm3 had a lower risk of LTP (p = .006).Conclusions Both MWA and PS treatments for large hepatic hemangioma are safe and effective, with MWA being superior in terms of efficacy.